Status of the Hungarian Agricultural Higher Education - Herman, Sándor; Körösparti, Péter; Kőmíves, Péter Miklós (International Journal of Engineering and Management Sciences, 2018)
In our article we are publishing a brief overview on the actual status of the Hungarian agriculture and agricultural higher education. We are presenting the changes of the agrieconomy in several economies of the world and the actual economic status of the Hungarian agriculture as well. We are showing the education level and the age of the employees working in the agriculture. We are presenting some information about the agircultural higher education, and some problems and perspectives of the investigated sector.